Peran Medan Talk Dalam Memenuhi Kebutuhan Informasi Masyarakat Kota Medan - Nurul Sakinah; Abdul Karim Batubara (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2023)
Instagram is a social media platform to access the latest information needs. Instagram social media usage is more than the use of print media. This study was conducted to determine how the effect of using online media on fulfilling information Needs on followers of @medantalk Instagram account. Instagram @medantalk is an Instagram social media account that conveys various information about events and circumstances that occur in the city of Medan, be it about tourist attractions, culinary, accidents, crime and so on. The purpose of this study was to determine and analyze how the effect of using online media on fulfilling information needs on followers of the @medantalk Instagram account. The results of the multiple linear regression analysis test indicate that the variable that has the most influence on the next information need variable (Y) is the brand image variable (X1) which is positive, while the variable use of Instagram (X2) has a positive effect, it can be said that the higher the variable use of Instagram, the greater the followers' information needs. Thus it can be said that brand image (X1) and Instagram usage (X2) together have a positive effect on information demand (Y).